Growth mechanism of aligned porous oxide layers on titanium by anodization in electrolyte containing Cl-. (2022) - Praharaj, Rinmayee; Mishra, Snigdha; Rautray, Tapash R.
Abstract: In recent times, fluoride-free electrolyte-based titanium dioxide nanotubes (TNTs) have been considered as the fourth generation synthesis method employing HCl, HClO4, H2 O2 solution and their mixture. In the present investigation, aligned porous oxide layers were achieved using chloride-based electrolyte in combination with polyethylene glycol and hydrogen peroxide through electrochemical anodization. In this method, H2 O2 was used instead of H2 O as an oxygen source. It was observed that oxidation of titanium was rapid in PEG/NH4 Cl/H2 O2 electrolyte. The fabricated oxide layer showed an amorphous structure. These amorphous porous oxide layers were then transformed into crystallized form by annealed at 500 °C for 2 h. The structural, morphological, and elemental analyses were carried out by X-ray diffraction, Field emission - scanning electron microscopy and Energy dispersive X-ray fluorescence. The X-ray diffraction pattern confirmed mixed phases of titania, and the average crystallite size was 31.72 nm. The Field emission - scanning electron microscopy morphologies showed aligned porous oxide arrays with smooth walls, and bundles of nanostructures were also observed. The EDX spectra indicated that the main components are O and Ti, with low content of Cl. It was observed that anodization in a chloride-containing organic electrolyte under a specific condition can be used to obtain higher-order titania nanostructure.